2009
DOI: 10.1161/circgenetics.109.874412
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of Genome-Wide Significant Single-Nucleotide Polymorphisms and Antiretroviral Therapy to Dyslipidemia in HIV-Infected Individuals

Abstract: the Swiss HIV Cohort StudyBackground-HIV-infected individuals have an increased risk of myocardial infarction. Antiretroviral therapy (ART) is regarded as a major determinant of dyslipidemia in HIV-infected individuals. Previous genetic studies have been limited by the validity of the single-nucleotide polymorphisms (SNPs) interrogated and by cross-sectional design. Recent genome-wide association studies have reliably associated common SNPs to dyslipidemia in the general population. Methods and Results-We vali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
40
2

Year Published

2010
2010
2025
2025

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 41 publications
(45 citation statements)
references
References 50 publications
3
40
2
Order By: Relevance
“…Studies of genetic polymorphisms may help to identify HIVinfected patients under antiretroviral therapy (ART) at higher risk for metabolic complications (12)(13)(14). Moreover, gene expression studies of subcutaneous adipose tissue may help us to better understand the mechanisms behind body fat changes in HIV-infected patients who initiate ART.…”
mentioning
confidence: 99%
“…Studies of genetic polymorphisms may help to identify HIVinfected patients under antiretroviral therapy (ART) at higher risk for metabolic complications (12)(13)(14). Moreover, gene expression studies of subcutaneous adipose tissue may help us to better understand the mechanisms behind body fat changes in HIV-infected patients who initiate ART.…”
mentioning
confidence: 99%
“…A study with the Swiss cohort assessed the contribution of 43 polymorphisms, 33 of which were identified through genome-wide association studies, to dyslipidemia in 745 HIV-infected patients on HAART. The results indicated that the host genetic variants assessed explained up to 7.6% variation in non HDL-C levels, up to 6.2% variation in HDL-C levels and up to 6.8% variation in TGC levels through the study [41]. These percentages were slightly greater than those resulting from the effect of antiretroviral treatment.…”
Section: Multi-gene Modelsmentioning
confidence: 87%
“…The complex polygenic trait of dyslipidemia among the HIV-1-infected individuals has been demonstrated by a genome-wide study association (GWSA) that evaluated the contribution of 42 different SNPs and other variables, such as HAART, underlying conditions, sex, age, ethnicity, and HIV-1 disease parameters to dyslipidemia in 745 HIV-infected participants [47]. The results showed that the genetic background alone explained up to 7.6% of lipid variation in HIV-1-infected patients (7.6% non HDL-C, 6.2% HDL-C, and 6.8% TG), and HAART alone explained up to 6.2% of lipid variation (3.9% non HDL-C, 1.5% HDL-C, and 6.2% TG).…”
Section: Discussionmentioning
confidence: 99%